A Note on Reducing Subspaces of Toeplitz Operator on the Weighted Analytic Function Spaces of the Bidisk Hw2D2. (7th May 2017) - Lin, Hongzhao
Abstract : We discussed the reducing subspaces of Toeplitz operators T z 1 N z 2 M     N ≠ M on the weighted analytic function spaces of bidisk H w 2 ( D 2 ) . The result shows that if the weight w is of type-I, the structure of reducing subspaces of T z 1 N z 2 M     N ≠ M on H w 2 D 2 is very simple.